Restricting Access: A Secondary Analysis of Scope of Practice Laws and Pre-exposure Prophylaxis Prescribing in the United States, 2017. (3rd January 2022) - Carnes, Neal; Zhang, Jun; Gelaude, Deborah; Huang, Ya-lin A.; Mizuno, Yuko; Hoover, Karen W.
Abstract: To assess advanced practitioners' scope of practice laws (i.e., legal authority providers can prescribe regulated medications) as potential barriers to HIV pre-exposure prophylaxis (PrEP), we conducted an analysis using IQVIA Real World Data in association with scope of practice law classifications supplied by the American Association of Nurse Practitioners and scopeofpracticepolicy.org . Nurse practitioners in states that allowed independent scope of practice were 1.4 times more likely to have prescribed PrEP compared with nurse practitioners in states where their prescribing authority is determined by a supervising medical doctor (MD). Physician assistants in states where the law or a state board defined their prescribing authority were more than twice as likely to prescribe PrEP compared with those in states where a supervising MD oversaw prescribing rights. Our findings suggest that restricting scope of prescribing practice by requiring MD oversight limits PrEP access and poses a barrier to scaling up PrEP.